KEWENANGAN NOTARIS MENGESAHKAN PERJANJIAN KAWIN SEBAGAI AMANAT KONSTITUSI - Firman Floranta Adonara; Ayu Citra Santyaningtyas (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2022)
The regulation in the Marriage Law Chapter 29 Verse (1) after Constitutional Court Decision Number 69/PUU/XII/2015 has been change into the process of marriage agreement. In the marriage agreement that legalized into Constitutional Court Number 69/PUU/XII/2015 can only be made before the marriage takes place. However, when the Constitutional Court Decision Number 69/PUU/XII/2015 arrives, a marriage agreement can be made as long as the marriage has taken place. The decision of the Constitutional Court Number 69/PUU/XII/2015 also gives a new authority to the Notary to be able to ratify the marriage agreement. Article 29 paragraph (1) of the Marriage Law after the Constitutional Court Decision Number 69/PUU/XII/2015 has provided changes after the Constitutional Court Decision Number 69/PUU/XII/2015 regarding the form of the marriage agreement in the form of a written agreement and must be ratified by the employee The marriage registrar has often been misinterpreted as an authentic deed, resulting in disharmony of implementing regulations related to the form of the marriage agreement.